Foci of Programmed Cell Death-Ligand 1 (PD-L1)-positive Tumor Areas With Tumor-infiltrating Leukocytes (TILs) Evocative of a PD-1/PD-L1-related Adaptive Immune Resistance are Frequent in Merkel Cell Carcinoma. Issue 1 (January 2020) - Bénigni, Paolo; Guénolé, Morgan; Bonsang, Benjamin; Marcorelles, Pascale; Schick, Ulrike; Uguen, Arnaud
Abstract : Immune checkpoint inhibitors (ICIs) targeting the programmed cell death 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) axis have revolutionized the treatment of patients with Merkel cell carcinoma (MCC). To date, no biomarker conditions access to these ICIs in MCC. We compared the tumor microenvironment of PD-L1 + and PD-L1 − areas in a case series of MCC searching for foci evocative of PD-1/PD-L1 adaptive immune resistance. Among 58 tumors studied on digitalized serial tissue sections, 11 (19%) were concluded as "PD-L1 + tumors" [≥1% positive tumor cells (TCs) using PD-L1 immunohistochemistry in the whole tumor slide]. In addition, among the remaining 47 (81%) "PD-L1 − tumors, " we nevertheless also identified "PD-L1 + FOV" (ie, "field of view" of about 3 mm² containing ≥1% positive TCs) in 22 (38%) additional tumors. Comparison between paired "PD-L1 + field of view (FOV)" and "PD-L1 − FOV" within tumors, and between "PD-L1 + tumors" and "PD-L1 − tumors", revealed correlations between PD-L1 positivity and the abundance of tumor-infiltrating leukocytes, arguing for areas of PD-1/PD-L1-related adaptive immune resistance at least in some foci of "PD-L1 + tumors" and also in "PD-L1 − tumors." Tumor heterogeneity consists in a challenge searching for biomarkers able to predict the response/nonresponse to ICIs. Progress in digital pathology and multiplex immunolabeling may permit to overcome this challenge by better analyzing the interactions between TCs and immune and nonimmune non-TCs in the same tissue section. This approach of tumor heterogeneity may contribute to elucidate and to predict why some patients respond impressively to ICIs, whereas others do not.